Information technology in pharmacy : an integrated approach - Goundrey-Smith, Stephen (London, United Kingdom : Springer, 2013)
The purpose of this book is to provide a general introduction to pharmacy information technology at the current time, to discuss issues surrounding the adoption of technology and to discuss how technologies may be utilised by the pharmacy profession to exercise new professional roles and achieve new professional aspirations.
IT Enabling Pharmacy Practice -- Electronic Patient Records -- Electronic Prescribing and Medicines Administration in Hospitals -- Pharmacy Automation -- Electronic Medicines Management in Primary Care -- Pharmacy Management Systems -- Barcodes and Logistics -- Future Prospects in Pharmacy IT
Includes index.
Keywords: CLINICAL PHARMACY INFORMATION SYSTEMS